Manhaj al-tadafu' fi al-mujtama' al-bashari (منهج التدافع في المجتمع البشري : دراسة تحليلية في أصول الصراع) - Ahmed Shogar, Ibrahim Adam (Centre fo Dawa and Community Development- International University of Africa-Sudan, 2007)
Throughout human history, conflict has been the human experience. We are now living in global era and changing world, but the potential to destroy is the certain fact that ever-increasing in step with the technological revolution. Parallel to this was great contributions has been made for understanding of conflict as a social interaction phenomena, and of equal importance efforts has been made to conflict resolution, particularly in Social psychology. The Holly Qur`an on the other hand, had provided the humanity with useful potentials and concepts concerning conflict and conflict resolution. The study, analytically, has addressed this issue at its genesis and root causes dimensions. Theoretically, socio-psychological theories and Qur`anic concepts has been used to discover roots or fundamental causes of conflicts and conflict resolutions. The discussion has concluded that conflict is a social phenomena which might not be avoided forever but it is, of course, can be managed by peaceful means that might be attained through recognition and management of four fundamental reasons of conflicts: interest, power, freedom o, and fulfillment of basic human needs. بمنهج تحليلي متكامل بين المفاهيم القرآنية و مقررات النظريات الوضعية تناول هذا البحث تمع البشري في أصوله العامة على مستو بين: موضوع التدافع أو مشكلة (الصراع) في ا مستوى نظري وآخر تطبيقي. أما في المستوى الأول فقد تعرض البحث، إلى جانب طبيعة ا